THE INFLUENCE OF SELF ASSESSMENT SYSTEM, TAX KNOWLEDGE ON TAXPAYER COMPLIANCE WITH TAX SANCTIONS AS A MODERATION VARIABLE IN KPP PRATAMA SOUTH MAKASSAR - Intan Febrianti; Haliah; Nirwana (CV. Radja Publika, 2024)
This research aims to examine the effect of the Self Assessment System, Tax Knowledge on Taxpayer Compliance with Tax Sanctions as a Moderating Variable at KPP Pratama South Makassar. The population of this research is taxpayers registered at KPP Pratama South Makassar. In selecting the sample we used the Slovin formula so that the total sample obtained was 100 taxpayers. This research uses field research methods. The type of data we use in this research is quantitative data, while the data source is primary data. To collect field data, this research used a survey method by distributing questionnaires. The statistical method used to test the hypothesis is to use SEM with the help of the Smart PLS program. The results of the analysis show that the self-assessment system and tax knowledge have a positive and significant influence on taxpayer compliance, while the moderating variable in this research, namely tax sanctions, strengthens the influence of self-assessment. tax systems and knowledge on taxpayer compliance.